The Positive Rate of Pulmonary Embolism by CT Pulmonary Angiography Is High in an Emergency Department, even in Low-Risk or Young Patients - Al-Zaher, Nizam; Vitali, Francesco; Neurath, Markus; Görtz, Rüdiger (Medical Principles and Practice, 2021)
Objective: The clinical presentation of pulmonary embolism (PE) can be various and misleading. We analyzed patients with suspicion of PE and subsequently performed computed tomography pulmonary angiography (CTPA) in an emergency department of Internal Medicine, focusing on patient groups in which PE might be underestimated in the emergency setting, such as young patients and patients with low clinical probability. Material and Methods: In 2016 and 2017, all patients receiving a CTPA for investigation of PE were retrospectively evaluated for clinical parameters (age, symptoms, and vital parameters) and D-dimers. The Wells score was calculated. Results: CTPA was performed in 323 patients (158 female and 165 male; mean age 62 years). The leading symptoms for admission were dyspnea or chest pain; 62% showed intermediate or high risk for PE, calculated by applying the Wells score. In 123 (38%) of all patients, a PE was proved and pathologic age-Adjusted D-dimers were found in 97.6%. Thirty of 121 (25%) patients with low risk according to Wells score had a PE. Deep vein thrombosis was verified in 67/123 (55%) patients; 43% (15/35) of all suspicions for PE in patients <40 years were positive with 4/15 (26%), showing a central PE. Younger patients (<40 years) with PE presented more often with tachycardia or tachypnea and chest pain or dyspnea than elderly patients with PE. Conclusion: CTPA frequently proves a PE in patients with suspicion of PE in an emergency department of Internal Medicine. If PE is suspected and CTPA performed accordingly, the presence of PE is quite common even in low-risk patient groups (Wells score) or in young patients <40 years with chest pain or dyspnea.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Chest pain; CT pulmonary angiography; Dyspnea; Emergency; Pulmonary embolisms